2018
DOI: 10.1042/bsr20171688
|View full text |Cite
|
Sign up to set email alerts
|

The intragenic epistatic association of ADD3 with biliary atresia in Southern Han Chinese population

Abstract: Biliary atresia (BA) is a multifactorial pathogenic disease with possible genetic components. As a member of membrane skeletal proteins in the liver and bile ducts, a haplotype composed by five single nucleotide polymorphisms (SNPs) on adducin 3 (ADD3) has been identified as associated with BA. However, limited study was designed to further elaborate the mutual relationship amongst those replicated SNPs to disease. We selected three susceptibility SNPs in ADD3 and conducted a replication study using 510 BA cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…Through a previous GWAS on Han Chinese, Cheng et al [25] discovered the correlation of the 10q24.2 region encompassing ADD3 and XPNPEP1 genes, which was confirmed in Chinese and Thai populations. Our earlier study also revealed the intragenic epistatic association of ADD3 with BA in Southern Han Chinese population [26].…”
Section: Discussionsupporting
confidence: 57%
“…Through a previous GWAS on Han Chinese, Cheng et al [25] discovered the correlation of the 10q24.2 region encompassing ADD3 and XPNPEP1 genes, which was confirmed in Chinese and Thai populations. Our earlier study also revealed the intragenic epistatic association of ADD3 with BA in Southern Han Chinese population [26].…”
Section: Discussionsupporting
confidence: 57%
“…We incorporated the published data before 2015, the newly published data and our current data to perform a further meta-analysis. In Asian population, rs17095355 showed consistent significant association with BA [11,18,19,21]. Rs17095355 also showed significant association in European descent, but rs7099604 showed more significant association [20].…”
Section: Discussionmentioning
confidence: 74%
“…These foundings indicated that ADD3 was the BA susceptibility gene at 10q24.2. The association between rs17095355 of ADD3 and BA was investigated repeatedly in multiple studies from different population [11,[18][19][20][21], and a meta-analysis comprising six case-control studies before 2015 has been conducted [26]. We incorporated the published data before 2015, the newly published data and our current data to perform a further meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations